SYSTEM FOR FORMING THE COMMUNICATIVE ASPECT OF PROFESSIONAL COMPETENCE OF A MUSICIAN TEACHER - Munisa Fatkhullaeva (Web of Journals Publishing, 2023)
The article discusses the system for forming the communicative aspect of professional competence of a musician teacher.
Keywords: music, pedagogy, methodology, piano, pedagogical university.